(3CgejI GdJhLjg Gdegfj hGdGLJeGYjs - (3ecj, QLGAs ((3HjQhJs (3eQcR GdGHMGK aj eYgO GdYdhe GdGLJeGYjI aj GdLGeYI GddHfGfjIs, 2001)
(3GdEQTGO hGdJhLjg eTcdI JWQM faSgG hJWQM eYgG eSCdI efgLjI JQHW eG Hjf GdYdhe GdELJeGYjI hGdJQHhjI hGdfaSGfjI, hJdqM Ydi EYGOI GdfXQ aj OhQ GdeOQSI GdMGdj haj YdGbJgG HGdCSQI hHcGaI GdYedjGJ GdJQHhjI, aYfO GdJYQV dCj eda ELJeGYj jLH Cf ffWdb ef eHOC JhLjgj EQTGOj YGe dG jbJUQ OhQg Ydi GdCSQI Hd jLH Cf jHOC CjVG ef GdeOQSI(B. (3hEfWdGbG Edi gOa GdOQGSI, hgh YQV hGbY GdJhLjg Gdegfj hGdELJeGYj hCgejJg aj GdeOGQS GddHfGfjI, hdCf GdJhLjg gh LRA ef GdYedjI GdJQHhjI GdTGedI, JWQM GdOQGSI eGgjI JhGLO Yde GdfaS aj GdeOQSI? hGdYdGbI GdJj JLeY Yde GdfaS hYde GdJQHjI? EYoJeO efgL OQGSI GdMGdI, hESJNOeJ JbfjI GdedGMXI ddCSGJPI hGdehqLgjf, GdESJeGQI, GdebGHdI eY GdJdGejP hGdCgd, heY GdHOjd Yf GdeQTO GdfaSj, hCSGJPI aj GdeOGQS GdEHJOGFjI(B. (3XgQ hGbY GdJhLjg Gdegfj hGdELJeGYj ZjQ eJZjQ HGdELeGd, aGdMGdGJ eJfhYI hGdeOGQS eJfhYI aj efGWb eNJdaI ef dHfGf, hCf GdJcGed GdhXjaj ZjQ MGUd eG Hjf GdeOGQS hGdehqLg, aj MGd JhGLOg, ceG HjfJ GdfJGFL Cf dcd eQMdI YeQjI eTGcdgG, hdG jecf Gdbhd HCfg gfGc MGLI ddehLg aj GdeQMdI GdJcejdjI hGdKGfhjI (B((3eQGMd Sf GdeQGgbI(B) (3Ohf Cf fCHg HGdeQMdI GdJCSjSjI GdChdi hgj GdWahdI(B). (3cPdc XgQ ZjGH ddeQTO Ch GdehLg ZjGHG THg cdj Yf GdeOGQS GddHfGfjI, hQZe GdJMhd GdEjLGHj GdPj jecf Cf jMUd Ch Cf jchf bO MUd, agh dG jZWj (B2% (3ef GdeOGQS GdeHMhKI(B. (3ceG JHjf YOe EjdGA GdeOGQS aj dHfGf GdCgejI deKd gPG GdfhY ef GdJhLg, jbGHdg ZjGH GdENJUGU Ch GdJOQjH aj GdLGeYGJ(B.s
(3GdfhY (B: (3ebGds
Keywords: Orientation et Conseil; School guidance and counseling; (3GdJhLjg hGdEQTGO GdeOQSjs